What was behind the first recognition and characterization of autochthonous SARS‐CoV‐2 transmission in Italy: The impact on European scenario. Issue 6 (6th May 2021) - Micheli, Valeria; Mancon, Alessandro; Malara, Annalisa; Mileto, Davide; Villani, Pier Giorgio; Rizzo, Alberto; Pagani, Cristina; Alquati, Omar; Gismondo, Maria Rita
Abstract: An Italian male with no link to China Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) epidemic presented at Emergency Room (ER) with severe respiratory impairment. The RT‐PCR on 20 February 2020, nasopharyngeal swab revealed SARS‐CoV‐2 infection, confirmed with viral culture and sequencing. This was the first identified autochthonous SARS‐CoV‐2 transmission in Italy, that unveiled global pathogen diffusion. This clinical case highlights an underestimation of SARS‐CoV‐2 circulation, making initial containment measures unfit to face the real situation and delaying the management of potentially affected SARS‐CoV‐2 patients.